Measuring Health System Efficiency; A Protocol Study - Farhad Hosseinzadeh Lotfi; Alireza Olyaeemanesh; Efat Mohamadi; Reza Majdzadeh; Ali Akbari Sari; Iraj Harirchi; AliAkbar Haghdoost; Hamid Sharafi; Haniye Sadat Sajadi; Zahra Goodarzi; Somayeh Noori Hekmat; Mohammad Mehdi Kiani; et al. (Health Technology Assessment in Action, 2022)
Abstract Background: To improve healthcare services’ quality, countries should measure their health systems’ efficiency and performance by robust methods. Objectives: We aimed to develop a national study to measure the efficiency of the health system in Iran. Methods: The literature review identified several methods for measuring efficiency; the most common one was data envelopment analysis (DEA). We adopted DEA, but its findings were simplistic and inaccurate, so we began to modify the method by determining the weight of each indicator. We identified the efficiency measurement indicators, in line with international standards and uniformed units, and then readjusted our input/output indicators according to the study context through four expert panels. We collected data and classified the input/output indicators, followed by determining each indicator’s weight and standard limits. Then we rationalized our previous results by applying the revised model. The initial new results of the refined model were valid, accurate, and consistent with previous studies, as approved by experts. We defined proper modeling to achieve the stated objectives. After investigating various DEA models, we finally designed a new model that was consistent with the existing data and conditions, entitled EDEA (extended DEA), to analyze other subprojects. Conclusions: The conventional DEA methods may not be accurate enough to measure health systems’ efficiency. By modifying modeling process, we propose a modified DEA with a very low error rate. We suggest that others interested in measuring health system efficiency adopt our modified approach to increase accuracy and create more meaningful policy-oriented results. Keywords: Efficiency; Health System; Productivity; Protocol